Arthrobotrys mendozadegivensis sp. nov. (Fungi: Orbiliales) from Mexico: Predatory Activity and Nematocidal Activity of Its Liquid Culture Filtrates Against Haemonchus contortus (Nematoda: Trichostrongylidae) - Enrique Gutiérrez-Medina; Pedro Mendoza-de Gives; Gustavo Pérez-Anzúrez; Antonio Colinas-Picazo; Génesis Andrea Bautista-García; Miguel Ángel Alonso-Díaz; Elke von Son-de Fernex; María Eugenia López-Arellano (Journal of Fungi)
During the isolation, identification, and assessment of nematode-trapping fungi (NTF) against nematodes, we discovered an unusual fungus in decaying wood from Morelos State, Mexico. This isolate exhibited some characteristics similar to those of the Arthrobotrys genus; however, we found that it did not match any previously reported species within this genus after conducting morphological and phylogenetic analyses using the ITS, TEF, and RPB2 regions. This new species displays conidiophores with two or three stems emerging from the same initial site and conidiophores with only a single stem and aerial thickened hyphae from which single conidiophores emerge, forming 3D adhesive nets. The conidia, which have one or two septa, range from obovoid to ellipsoidal, crowned by four to six conidia. This report provides evidence that this species has not been described before, and we hereby introduce it as a new species, naming it Arthrobotrys mendozadegivensis. This species displayed a predatory activity of 76.92%, and its liquid culture filtrates in Sweet Potato Dextrose Broth and Czapek–Dox Broth were effective in killing 40.90% and 34.91% of Haemonchus contortus larvae, respectively. This study provides information about a previously unreported species of nematophagous fungus, which is important for systematics and has potential biotechnological applications against nematodes that affect the livestock industry.